Investigating the recovery period of rat brain tissue after electrolytic and 980-nm laser induced lesions - (:unkn) unknown (SPIE, 2003)
The effects of 980-nm diode laser and electrolytic lesions in Wistar rat brain tissue were observed by immunohistochemical staining for CD68 marker and Hematoxylin-Eosin (H&E). Bilateral lesions; laser lesions (2W/2sec) in the right hemispheres, and electrolytic lesions (1.5mA/20sec) in the left hemispheres were done through in vivo stereotaxic neurosurgical procedure. Subjects were classified into three groups due to the recovery period. Subjects in Group I, II, and III were sacrificed after 0, 2 and 7 days of recovery period respectively. After saline perfusion their brains were dislocated, and paraffin embedded sections were taken. One section for H&E and one for CD68 were cut consecutively in 3μm thickness by examining the lesion in every 30-μm thickness. CD68 was found more efficient marker than H&E in observing the after-effects of both types of lesions. The total damage of laser was smaller than that of electrosurgical unit. The shape of the ablated area in laser induced lesions was more spherical than that of electrosurgical unit. The number of macrophages increased as the recovery period increased for all subjects. Group III showed the highest number of macrophages in three, and the number of macrophages around electrolytic lesion is nearly 1.5 times higher than that of laser lesion. The remarkable ablating ability, the damage zone created and the healing of nearby tissue clearly showed that the 980-nm diode laser is an effective and useful alternative to electrosurgical unit in neurosurgery.
Keywords: 980-nm diode laser lesion; CD68; Electrocoagulation; Hematoxylin-eosin; Laser tissue interaction; Macrophage; Stereotaxic surgery